“I think it was in poor taste that you were doing Murtaugh in whiteface” – Blackface goes West (and White) in It’s Always Sunny in Philadelphia (FX, 2005-) - Sébastien Lefait (Revue LISA)
As many academics have shown, blackface minstrelsy is a distorted view of the South developed mainly in the North of the United States. To contradict the notion that the blackface tradition can exclusively travel following a South/North axis, this article considers how this tradition has recently applied to the West of cowboys and Indians, and to their contemporary siblings, the cops and villains of action movies. Two episodes of It’s Always Sunny in Philadelphia (s06e09 and s09e09) offer cases in point. In these two installments, a white character “blacks up” to play Murtaugh in “sweded” sequels to Lethal Weapon 1 to 4 (Richard Donner, 1987, 1989, 1992, 1998). In these films within the series, the blackface tradition evolves to debunk other stereotypes than those it traditionally targets. One of them is embodied by the villainous “Chief Lazarus,” a Native Indian chief played by Frank Reynolds (Danny De Vito). Analysis of key sequences in the episodes shows that the Southern/Northern blackface may go west to expose persistent Western movie clichés, and to expose derivatives such as “whiteface,” “redface,” “bimboface,” or even “gayface.” Finally, the series ascribes these evolutions of the blackface trope to major aspects of contemporary visual culture, and to the current rise of white supremacist ideology.